Association of IGF and IGFBP2 gene polymorphisms with growth and egg traits in Atak-S laying hens - DAŞ, H.; TARIM, B.; DEMIR, S.; KÜÇÜKKENT, N.; CENGIZ, S.; TÜLEK, E.; AKSAKAL, V. (Journal of the Hellenic Veterinary Medical Society, 2018)
Atak-S laying hens are a high-performance hybrid obtained by crossing of the Rhode Island Red (RIR) X the Barred Plymouth Rock (BR) and are being produced in the Ankara Poultry Research Institute since 1997. Phenotypic and genetic improving studies are continuous for this hybrid. In this study three different SNPs, two from IGF1 and one from IGFBP2 genes, were examined in 150 Atak-S chickens. Genetic association of SNPs were compared to body weight and egg number till 32 weeks of age, body weight at sexual maturity, age at sexual maturity and also egg quality traits such as egg shell breaking strength, shell thickness, Haugh unit, albumen index, yolk index and shape index were statistically analyzed. Only IGF1(a) locus was in agreement with Hardy-Weinberg equilibrium, while, the rest of the loci were not. As a result of the comparisons performed to the three SNPs, it was determined that there was a significant association (P<0.05) between the T364C haplotypes of the IGF1(b) locus and body weight at 32 weeks of age, but there was not any association to the other traits.